Поняття «трудові правовідносини з поліцейськими» - Бортник, С. М.; Bortnik, S. M.; ResearcherID: AAB-6020-2020; Serhii Bortnyk (Вісник Харківського національного університету внутрішніх справ. - 2017. - № 2 (77). - С. 11-18, 2017)
Проаналізовано наукові підходи до визначення поняття «трудові правовідносини». Розглянуто структурні елементи трудового правовідношення, проаналізовано підстави виникнення трудових правовідносин. Досліджено особливості трудових правовідносин із поліцейськими. Надано авторське визначення поняття «трудові правовідносини з поліцейськими».

The author of the article has analyzed the scientific approaches to determining the concept of “labor legal relations”. Structural elements of labor legal relations have been considered, the reasons of the origin of labor legal relations have been analyzed. The features of labor legal relations with the police officers have been studied. Special attention has been paid to the fact that the police officers are specific subjects both of labor law and labor legal relations. This specificity is due to the functions and tasks of the police and to the nature of the activities. It has been noted that the employer within the studied relations is the state, and the police acts on its behalf. The author has specified on the duality of the status of the head of a police agency: on the one hand – as a representative of the employer, i.e. the police agency, on the other – as a police officer. The object of labor legal relations with the police officers is the actual process of service and financial support that a police officer gets for it. The author argues that the order on the appointment to the police position should be regarded as the main and independent constitutive legal fact, because the origin of labor legal relations with the police officers is associated to its publication. The author has provided own definition of the concept of labor legal relations with the police officers – that is a legal relationship of a police officer and the state, where the police acts on behalf of the state, concerning the service and salaries arising on the basis of the order about the appointment.

Проанализированы научные подходы к определению понятия «трудовые правоотношения». Рассмотрены структурные элементы трудового правоотношения, проанализированы основания возникновения трудовых правоотношений. Исследованы особенности трудовых правоотношений с полицейскими. Дано авторское определение понятия «трудовые правоотношения с полицейскими».
The term “labor legal relations with the police officers”
Понятие «трудовые правоотношения с полицейскими»
Keywords: Трудове право. Право соціального забезпечення. Labor law. Law of social guaranteeing. Трудовое право. Право социального обеспечения; Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; поліція; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; Internal Affairs Agencies; органы внутренних дел; трудові правовідносини; поліцейський; працівник; роботодавець; працівник поліції; labor legal relations; police officers; police; employee; employer; трудовые правоотношения; полицейский; работник; работодатель